Analisis Pengelompokan Karakter Pemain Usia Dini di Sekolah Futsal Golden Eagles Berdasarkan Faktor Perilaku Menggunakan Algoritma K-means - Abdul Khoir; Muhamad Arifin Ilhan; Kevin Ananda Maas; Risca Lusiana Pratiwi; Euis Widanengsih (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze and categorize the character of young futsal players based on the results of coaches' assessments using the K-Means Clustering algorithm. Data were obtained from 70 Golden Eagles Futsal School students aged 5–13 years who were directly observed by coaches during routine training sessions. Assessment aspects included concentration, cooperation, discipline, enthusiasm, emotional control, and response to instructions. The analysis process was carried out using Python with the Scikit-learn library as the main tool for data processing and visualization of results (bar charts and heatmaps). The clustering results formed three main clusters: (1) independent and highly focused children, (2) developing children, and (3) children who require more attention. The average behavioral scores showed clear differences between clusters, with the first group having the highest levels of concentration and discipline. These findings indicate that a data-driven approach can provide a deep understanding of the character of young children in the context of futsal, as well as serve as a reference for coaches in designing more personalized and effective coaching strategies.